Mutual Fund Transparency and Corporate Myopia - Agarwal, Vikas; Vashishtha, Rahul; Venkatachalam, Mohan (Review of Financial Studies, 2018)
Pressure from institutional money managers to generate profits in the short run is often blamed for corporate myopia. Theoretical research suggests that money managers' short term focus stems from their career concerns and greater fund transparency can amplify these concerns. Using a difference-in-differences design around a regulatory shock that increased transparency about fund managers' portfolio choices, we examine whether increased transparency encourages myopic corporate investment behavior. We find that corporate innovation declines following the regulatory shock. Moreover, evidence from mutual fund trading behavior corroborates that these results are driven by increased short-term focus of money managers.